2020
DOI: 10.3390/ijms21165817
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Allergenic Potential in Bread Wheat RNAi Transgenic Lines Silenced for CM3, CM16 and 0.28 ATI Genes

Abstract: Although wheat is used worldwide as a staple food, it can give rise to adverse reactions, for which the triggering factors have not been identified yet. These reactions can be caused mainly by kernel proteins, both gluten and non-gluten proteins. Among these latter proteins, α-amylase/trypsin inhibitors (ATI) are involved in baker’s asthma and realistically in Non Celiac Wheat Sensitivity (NCWS). In this paper, we report characterization of three transgenic lines obtained from the bread wheat cultivar Bobwhite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Moreover, the genotype Timilia presents a much higher relative abundance of αamylase inhibitor 0.28 in comparison with the other two genotypes investigated here. This finding appears very interesting because this protein represents one of the non-gluten components, listed in the Allergome database (http://www.allergome.org/, accessed on date 8 February 2021), likely to be allergenic, and may have a role in nonceliac wheat sensitivity (NCWS) and celiac disease (CD) [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the genotype Timilia presents a much higher relative abundance of αamylase inhibitor 0.28 in comparison with the other two genotypes investigated here. This finding appears very interesting because this protein represents one of the non-gluten components, listed in the Allergome database (http://www.allergome.org/, accessed on date 8 February 2021), likely to be allergenic, and may have a role in nonceliac wheat sensitivity (NCWS) and celiac disease (CD) [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies helped to understand the complex gene network that regulates protein expression during grain development, the biochemical mechanisms for ATI synthesis still require further research. The complexity of trypsin inhibition was impressively demonstrated in a recent research study: although total ATI concentrations were reduced by gene silencing of three major ATI genes, TIA was increased [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the research in this field is rapidly increasing. Recently, two independent studies [ 206 , 207 ] reported CRISPR/Cas9 editing of the α-Amylase/Trypsin inhibitor (ATI) genes, reducing the allergen proteins in durum wheat. The ATI subunits WTAI-CM3 and WTAI-CM16 from the durum wheat cultivar Svevo were edited to produce lines with reduced allergens.…”
Section: Gene Editing In Durum Wheatmentioning
confidence: 99%